THE PHONO-SIGNOSEMANTIC ONTOLOGY OF MODERN ENGLISH “WILL” AND OTHER WORDS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Modern linguistics traditionally treats the link between word forms and meanings as arbitrary. In stark contrast, the emerging Odam Tili theory (from Uzbek “Odam Tili” meaning “Human Language”) proposes that language sounds and symbols are rooted in natural human experience [1][2]. Developed over two decades by Dr.